1500 Years of Pottery: Neutron Activation Analysis of Northern Chilean Domestic Ceramics from Caleta Vitor and Clay Samples from Nearby Valley, Coast and Highland Contexts. (16th December 2016) - Bland, C. A.; Roberts, A. L.; Popelka‐Filcoff, R. S.; Santoro, C. M.; Carter, C.; Bennett, J. W.; Stopic, A.
Abstract : This paper presents the findings arising from neutron activation analysis (NAA) of northern Chilean domestic ceramic samples from Caleta Vitor (n = 38) and clay samples (n = 15) from nearby valley, coast and highland contexts. This study presents the first NAA data set of ceramics spanning a temporal period of 1500 years (c.2000 to c.476 bp ) from the Vitor Valley as well as the first attempt to use NAA to characterize potential clay sources in the region. On the basis of this study, we argue that the majority of domestic ceramics from Caleta Vitor share compositional similarities with clay samples collected from nearby valleys, allowing us to infer that the Caleta Vitor populations primarily procured their clay for domestic ceramics from local sources throughout a 1500‐year period. Thus, despite the fact that there were inter‐regional interactions during this period that included the influence of powerful Andean polities, it would appear that domestic ceramics continued to be produced locally, and by implication it can be argued that such interactions did not substantially affect this sphere of material culture production. Further, the apparent continuities in domestic ceramic production allow us to reflect on local decision‐making processes throughout the cultural phases considered in this research.